(untitled) - Craul, Timothy A. (Hoboken, N.J., 2006)
Drawing on a wealth of experience in soils, forestry, micrometeorology, geomorphology, and agronomy, this book's authorial team presents: A succinct introduction to the physical and chemical properties that pertain to all planting soils; Informative descriptions of how a project evolves from site investigation to construction administration; Quick, easy-to-read procedures organized in the standard landscape architect stages of a project; Step-by-step templates to use from a project's inception to completion; The latest material on such specialized design elements as rooftops, intensely designed elements, and treatment wetlands, as well as pervious poured concrete, pervious pavers, and the supporting soil.
Keywords: Landscape design,Landscape contracting,Soil structure,Soil stabilization,Garden soils